Railway car body lateral hunting attenuation using body-based modified skyhook control for secondary suspension - Abdullah, Mohd Azman; Harun, Mohd Hanif; Ahmad, Fauzi; Mohamed Jamil, Fathiah; MUNALIZA BINTI IBRAHIM, MUNALIZA BINTI IBRAHIM (2022)
The unwanted lateral hunting on railway vehicle body will reduce the performance of railway vehicle ride comfort. Due to this, a simplified model of railway vehicle suspension with five degrees of freedom (5 DOF) is utilized to study the response of the railway vehicle body due to lateral track irregularities. A new body-based modified skyhook control algorithm is proposed in order to overcome the limitation of the passive system in absorbing the unwanted lateral disturbances from the track. The results of the presented scheme show an improvement in the performance of the proposed scheme when the railway vehicle running on an uneven track compared to a passive system.